Trajectory Planning of a Hexapod Robotic Kit - Masum, H (International Journal of Computer Sciences and Engineering, 2025)
Mode of locomotion of a robot can be chosen according to the condition of the terrain; these are wheeled, Legged and Crawler or Hybrid. Legged mobile robots are superior to conventional wheeled mobile robot (WMR) for rough and marshy terrain due to its terrain adaptability. They have also the ability to raise or lower bodies or tilt them by varying the length of its legs by bending knees. However, unlike WMR, legged robots are much complex and needs more comprehensive analysis for developing a realistic autonomous system. The goal of this research is to develop a path planning of powered and autonomous hexapod robotic kit which is capable of navigating different terrain within the mechanical motion limits. It has been observed that the kit is capable to take turn at sharp corner or when it needs to turn at a large angle at any instant.